Analgesic Efficacy of Quadratus Lumborum Block in Patients Undergoing Nephrectomy: A Systematic Review and Meta-Analysis. Issue 5 (2nd November 2022) - Wang, Jinxu; Chu, Tiantian; Sun, Rao; Xu, Aijun
Abstract: Objective: To evaluate the analgesic efficacy of quadratus lumborum block (QLB) in adults undergoing nephrectomy. Design: Systematic review and meta-analysis. Patients: Adult patients (≥18 years of age) received nephrectomy under general anesthesia. Methods: We searched PubMed, Embase, the Cochrane Library, and Web of Science on January 10, 2022, including randomized controlled trials that evaluated the analgesic efficacy of QLB for patients undergoing nephrectomy. Results: A total of 12 randomized controlled trials (N = 821 patients) were included in the study. Compared with the non-block, single-shot QLB reduced postoperative opioid consumption (mean difference [MD], −8.37 mg intravenous morphine equivalent; 95% confidence interval [CI], −12.19 to −4.54 mg) and pain scores at 2 hours, 6 hours, 12 hours, and 24 hours at rest and during movement after nephrectomy. Single-shot QLB also prolonged the time to first analgesic request (MD, 6.44 hours; 95% CI, 2.23 to 10.65 hours), shortened the length of hospital stay (MD, −0.32 day; 95% CI, −0.55 to −0.09 day), and decreased the incidence of postoperative nausea and vomiting (risk ratio, 0.48; 95% CI, 0.36 to 0.65). Compared with continuous epidural anesthesia, repeated QLB could provide comparable postoperative analgesic benefits. Conclusions: Single-shot QLB provided a statistically significant but clinically small improvement in postoperative analgesia and recovery for patients undergoing nephrectomy. The QLB would be beneficial as part of multimodal analgesia. Future research might need to determine which approach of QLB is superior for postoperative analgesia after nephrectomy.